Analysis of Financial System Modeling for Integrated Petty Cash Based on Business Process Management - Bagas Brian Pratama; Kurnia Ekasari; Andi Kusuma Indrawan (PT. EQUATOR SINAR AKADEMIA, 2022)
This study aimed to analyze the modeling of financial information systems for integrated petty cash using the concept of a Business Process Management System. The object of study was a training service company. This case study analysis was conducted to find problems in the study's object and then formulate. This study applied a qualitative method using Yin's (2009) explanatory case study analysis techniques with several stages ranging from data collection, case identification, and in-depth analysis to theory development and implications for settlement. The result of the study was a business process model based on Business Process Management Notation (BPMN) which could increase effectiveness and efficiency so that it had implications for improving the quality of the company's business processes.